STRATEGI PEMASARAN UNTUK PRODUK OLAHAN TOMAT DI ERA DIGITAL PASAR INPRES KOTA PALU - Wina Wina; Vidya Putri Aprilia; NurHusna Aulia; Syaiakbar Dirgantara Hariyanto; Ahmar Ahmar; Nuraisyah Nuraisyah; Andi Maman Firmansyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research focuses on formulating an effective marketing strategy for processed tomato products at the Inpres Market in Palu City with a focus on health aspects and product quality. The strategies that will be implemented include educating consumers about the health benefits of processed tomato products, developing innovative new products, and product certification to guarantee quality. Apart from that, promotions will be carried out through various digital channels and collaboration with local culinary businesses. This research aims to formulate an effective marketing strategy for processed tomato products in the digital era, especially in the Inpres Palu market. The proposed marketing strategy includes the use of social media, e-commerce development, and search engine optimization. It is hoped that the research results can contribute to tomato processing businesses and increase sales and expand market reach.